A domesticated photoautotrophic microbial community as a biofilm model system for analyzing the influence of plastic surfaces on invertebrate grazers in limnic environments - Bakenhus, Insa; Jongsma, Rense; Michler-Kozma, Diana; Hölscher, Lea; Gabel, Friederike; Holert, Johannes; Philipp, Bodo (Frontiers in Microbiology, 2023)
The environmental fate of plastic particles in water bodies is influenced by microbial biofilm formation.Invertebrate grazers may be affected when foraging biofilms on plastics compared to biofilms on natural substrata but the mechanistic basis for these effects is unknown. For analyzing these effects in ecotoxicological assays stable and reproducible biofilm communities are required that are related to the environmental site of interest. Here, a defined biofilm community was established and used to perform grazing experiments with a freshwater snail. For this, snippets of different plastic materials were incubated in the photic zone of three different freshwater sites. Amplicon sequencing of biofilms formed on these snippets showed that the site of incubation and not the plastic material dominated the microbial community composition. From these biofilms, individual microbial strains as well as photoautotrophic consortia were isolated; these consortia consisted of heterotrophic bacteria that were apparently nourished by microalga. While biofilms formed by defined dual cultures of a microalga and an Alphaproteobacterium were not accepted by the snail P. fontinalis, a photoautotrophic consortium (Co_3) sustained growth and metabolism of this grazer. Amplicon sequencing revealed that consortium Co_3, which could be stably maintained on solid medium under photoautotrophic conditions, reproducibly formed biofilms of a defined composition on three different plastic materials and on glass surfaces. In conclusion, our study shows that the generation of domesticated photoautotrophic microbial communities is a valid novel approach for establishing laboratory ecotoxicological assays with higher environmental relevance than those based on defined microbiota.